2020
DOI: 10.1088/1748-9326/aba6ae
|View full text |Cite
|
Sign up to set email alerts
|

Effect of WWTP size on grey water footprint—Czech Republic case study

Abstract: The number of wastewater treatment plants (WWTPs) in the Czech Republic is increasing. Wastewater, which was previously disposed of in other ways (e.g. septic tanks, cesspits etc), is now entering the surface water (after treatment at a WWTP). Billions of Czech crowns have been invested in the construction of new WWTPs or reconstruction and intensification of existing ones. This money had been invested to meet discharge standards for individual pollutants. However, the overall level of pollution associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…The highest value of the GWF has ammonium nitrogen. Another study assessing all major wastewater treatment plants in the Czech Republic also showed that ammonium nitrogen is a parameter that usually has the highest value of GWF (Ansorge, Stejskalová, and Dlabal 2020b). Nevertheless, the parameter of ammonium nitrogen (in accordance with Czech regulations) is not included in discharge permits.…”
Section: Discussionmentioning
confidence: 99%
“…The highest value of the GWF has ammonium nitrogen. Another study assessing all major wastewater treatment plants in the Czech Republic also showed that ammonium nitrogen is a parameter that usually has the highest value of GWF (Ansorge, Stejskalová, and Dlabal 2020b). Nevertheless, the parameter of ammonium nitrogen (in accordance with Czech regulations) is not included in discharge permits.…”
Section: Discussionmentioning
confidence: 99%
“…It makes the trend of the industrial and domestic grey water footprint in Yantai converge with the changing trend of pollutant emission. Therefore, controlling the discharge of pollutants, strengthening the management of sewage treatment plants, and improving wastewater treatment capacity is particularly important for reducing the grey water footprint [51,52].…”
Section: Grey Water Footprintmentioning
confidence: 99%
“…We focused on the two key pollutants discharged from WWTPs, total phosphorous (P) and ammonium-nitrogen (NH4N), whose values are established proxies for ecological risks in receiving river bodies (Ansorge et al, 2020). However, the approach can be applied to any other pollutants of known per capita loadings discharged from WWTPs.…”
Section: Local-scale Mixing Concentrations Of Pollutants In Receiving...mentioning
confidence: 99%